Endoscopic drainage and one-stage titanium clip closure for appendiceal root abscess mimicking cecal submucosal tumor: a case report - Yanping Dai; Yang Liu; Jun Ye (Frontiers in Medicine, 2026)
Periappendiceal abscess stands as a frequent complication stemming from acute appendicitis. One rare variant presents as a submucosal mass at the root of the appendix and cecum. Clinicians often misdiagnose this form at alarmingly high rates. Conventional management brings substantial surgical trauma. It also prolongs patients’ recovery periods. Whether minimally invasive endoscopic intervention works well for this distinct abscess subtype still lacks solid clinical proof. Whether minimally invasive endoscopic intervention works well for this distinct abscess subtype still lacks solid clinical proof. This report documents a single case of a 34-year-old female patient. Dull epigastric pain served as her chief complaint. Initial colonoscopy spotted a submucosal lesion around the appendiceal orifice. Contrast-enhanced abdominal CT and endoscopic ultrasonography (EUS) followed afterward. Combined with the golden diagnostic evidence of purulent fluid extruded by gentle intraoperative compression on the lesion, a definitive diagnosis of localized periappendiceal abscess confined to the appendiceal base was confirmed. Endoscopic incision and drainage were performed for lesion decompression. A tiny perforation measuring 3 mm emerged mid-procedure. Clinicians sealed the defect primarily with titanium clips. Abdominal paracentesis was applied concurrently to evacuate intraperitoneal gas. The patient recovered uneventfully after the operation. This atypical periappendiceal abscess easily mimics submucosal neoplasms, which raises diagnostic confusion. Endoscopic ultrasonography acts as the pivotal tool to achieve accurate differentiation. Endoscopic minimally invasive drainage delivers reliable safety and therapeutic efficacy. Intraoperative micro-perforations can be closed in one session via endoscopy. This strategy eliminates the need for open surgery. Its prominent minimally invasive merits make the technique worthy of broader clinical adoption.